Early biomimetic degradation of Mg-2Ca alloy reveals the impact of β-phases at the interface of this biomaterial on a micro-scale level. (October 2022) - Bexiga, Nuno M.; Alves, Marta M.; Taryba, Maryna G.; Pinto, Sandra N.; Montemor, M.F.
Abstract: Despite several studies on Mg-Ca alloys as bone implants, the understanding of its early degradation in the first hours of immersion is still lacking. To overcome this gap, advanced localized electrochemical techniques were used to study the corrosion onset of Mg-2Ca alloy 2 h upon immersion. The presence of the nobler β-phase induced Mg dissolution from the matrix, an event supporting the positive response of osteoblast stem cells. This, together with apatite precipitation within the corrosion layer highlights the potential of Mg-2Ca for bone implants. The data gathered in this work contribute to tailoring the design of new Mg-Ca alloys. Graphical Abstract: ga1 Highlights: Degradation events that can modulate material-cell interaction were observed during the first 2 h of immersion. The potential difference between less noble Mg matrix and more noble Mg2 Ca guided the onset of degradation. Mg dissolution from the matrix, induced by the nobler β-phase, can be related to an increase in fibroblasts viability. Alkaline pH spreading in a range of ~50 µm from the β-phases can influence cells' adhesion on the surface